Factors Affecting Outpatients Intention to Revisit Health Services at Public Health Center in Demak District - Lina Dwi Yoga Pramana; Antono Suryoputro; Cahya Tri Purnami (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The pandemic situation led decreasing in the number of patient visits at Public Health Centers (PHC) due to concerns about contracting Covid-19, including in Demak District which experienced a decrease in visits to 71.7% from 141.2% in 2019. The lack of usage of health services contributed to the poor community health status. The purpose of the study was to analyze the influence of various factors regarding the intention of revisits health services at PHC in Demak District during the Covid-19 pandemic. This is quantitative research with a cross-sectional approach. The population were patients who visited PHC in Demak District. Samples determined by the purposive sampling technique amounted to 332 people. Partial effect test with simple linear regression and simultaneously with multiple linear regression because classical assumption test requirements were met. A total of 57.5% of respondents have a high intention to revisit health services. Partially it’s proven that knowledge, health workers' ability, infrastructure, service quality and waiting time affected intentions to revisit health services in PHC. Variables of waiting time, infrastructure, health workers' ability, and service quality were predictors for revisits with an overall effect of 27.7%. Health centres need to develop an online queuing mechanism to reduce waiting times and gradually equip infrastructure and improve service quality through health workers' discipline.Abstrak: Situasi pandemi menyebabkan penurunan jumlah kunjungan pasien di puskesmas karena kekuatiran tertular Covid-19, termasuk di Kabupaten Demak yang mengalami penurunan kunjungan menjadi 71,7% dari 141,2% di tahun 2019. Rendahnya perilaku pemanfaatan layanan kesehatan berkontribusi pada status kesehatan masyarakat yang tidak optimal. Tujuan penelitian menganalisis pengaruh berbagai faktor terhadap niat kunjungan ulang di puskesmas Kabupaten Demak selama pandemi Covid-19. Merupakan penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian yaitu seluruh pasien yang berkunjung di puskesmas di Kabupaten Demak. Sampel ditentukan dengan teknik purposive sampling berjumlah 332 orang. Uji pengaruh secara parsial dengan regresi linier sederhana dan simultan dengan regresi linier berganda karena persyaratan uji asumsi klasik terpenuhi. Sebanyak 57,5% responden memiliki niat tinggi melakukan kunjungan ulang. Secara parsial terbukti pengetahuan, kemampuan tenaga kesehatan, sarana prasarana, kualitas layanan dan waktu tunggu mempengaruhi niat kunjungan ulang di puskesmas. Waktu tunggu, sarana prasarana, kemampuan tenaga kesehatan dan kualitas pelayanan menjadi prediktor untuk niat kunjungan ulang dengan pengaruh keseluruhan sebesar 27,7%. Puskesmas perlu mengembangkan mekanisme antrian online untuk mengurangi waktu tunggu dan secara bertahap melengkapi sarana prasarana dan meningkatkan kualitas layanan melalui kedisiplinan tenaga kesehatan.